2014
DOI: 10.1352/1934-9556-52.5.330
|View full text |Cite
|
Sign up to set email alerts
|

Observation-centered Approach to ASD Assessment in Tanzania

Abstract: In many lower-income countries, there is a paucity of assessment services for autism spectrum disorders (ASD)., Guidelines will be provided for conducting cross-cultural assessments in the context of limited validated resources in Tanzania. By examining behavioral, social, and adaptive differences we were able to provide differential diagnostic evaluations aligning with best practice standards for 41 children in Tanzania age 2-21 years. We describe the utility of a flexible, behavioral observation instrument, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…It was reported that the 23-item questionnaire was modestly successful in identifying a subgroup of children at high risk of being diagnosed as having ASD. A study from Tanzania evaluated the potential use of the Childhood Autism Rating Scale to perform a structured observation to diagnose ASD [16]. In this study, the Childhood Autism Rating Scale was culturally adapted for use in Tanzania.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the 23-item questionnaire was modestly successful in identifying a subgroup of children at high risk of being diagnosed as having ASD. A study from Tanzania evaluated the potential use of the Childhood Autism Rating Scale to perform a structured observation to diagnose ASD [16]. In this study, the Childhood Autism Rating Scale was culturally adapted for use in Tanzania.…”
Section: Resultsmentioning
confidence: 99%
“…These challenges are the impetus towards the development and validation of tools in the African context. However, some studies [16, 17] present early, yet very crucial steps towards identification of potential screening and diagnostic tools for the African context. The need to invest more into this process cannot be overemphasized given the potential benefit in accessing tools that can contribute towards early identification of children who have ASD.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only two publications have focused specifically on ASD screening and diagnosis in SSA—one each from Tanzania and Uganda [Harrison, Zimak, Sheinkopf, Manji, & Morrow, ; Kakooza‐Mwesige et al, ]. Both studies were cross‐sectional.…”
Section: Screening and Diagnosis Of Asdmentioning
confidence: 99%
“…Both studies were cross‐sectional. In Tanzania, Harrison et al [] used the Childhood Autism Rating Scale, Second Edition (CARS‐2), an observational diagnostic aid for ASD [Schopler, Van Bourgondein, Wellman, & Love, ] as part of a larger test battery to diagnose ASD. A process of cultural adaptation of the test battery for the target population was described.…”
Section: Screening and Diagnosis Of Asdmentioning
confidence: 99%
“…Recently the CARS-2 (Schopler et al 2010) was chosen for use in a low resource setting in Tanzania (Harrison et al 2014). …”
Section: Introductionmentioning
confidence: 99%